2005
DOI: 10.1370/afm.239
|View full text |Cite
|
Sign up to set email alerts
|

The Recognition of Depression: The Primary Care Clinician's Perspective

Abstract: PURPOSE The purpose of this study was to explore the responses of primary care clinicians to patients who complain of symptoms that might indicate depression, to examine the clinical strategies used by clinicians to recognize depression, and to identify the conditions that infl uence their ability to do so. METHODSThe grounded theory method was used for data collection and analysis. In-depth, in-person interviews were conducted with a purposeful sample of 8 clinicians. All interviews were audiotaped and transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 46 publications
(37 reference statements)
2
53
0
3
Order By: Relevance
“…To describe the comprehensive model succinctly, processes and conditions are grouped into four depression care stages identified in the data: recognition ( Fig. 1), between recognition and initial treatment ( The Recognition of Depression: Figure 1 This study confirmed previously identified three processes (ruling out, opening the door, and recognizing the person) and three conditions (time, experience, and familiarity with the patient) 59 and dimensions of clinical experience that result in provider comfort, a potential mediating variable, in depression care. 60 Two other previously identified conditions (lack of objective evidence and stigma) were refined as clinical-related or system-related and society-related conditions, respectively.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…To describe the comprehensive model succinctly, processes and conditions are grouped into four depression care stages identified in the data: recognition ( Fig. 1), between recognition and initial treatment ( The Recognition of Depression: Figure 1 This study confirmed previously identified three processes (ruling out, opening the door, and recognizing the person) and three conditions (time, experience, and familiarity with the patient) 59 and dimensions of clinical experience that result in provider comfort, a potential mediating variable, in depression care. 60 Two other previously identified conditions (lack of objective evidence and stigma) were refined as clinical-related or system-related and society-related conditions, respectively.…”
Section: Resultssupporting
confidence: 68%
“…46 Consistent with those findings, we discovered that time constraints hindered even experienced clinicians' ability to deliver depression care, even with familiar patients. 58,59 Depression care quality interventions to date have tended to focus on larger practices that comprise about one-fourth of US PC practices. The other three-fourths of PC practices are individual or small group practices with scarcer resources.…”
Section: Discussionmentioning
confidence: 99%
“…Major depression is the leading cause of disability and the cause of more than two-thirds of suicides each year [1]. Therefore, failure to diagnose depression in primary care is a critical public health problem that results in high societal costs related to disability, morbidity, mortality, and excessive health care utilisation [2]. Moreover, effective depression treatment is limited by current assessment methods that rely almost exclusively on patient-reported or clinical judgements of symptom severity [3], risking a range of subjective biases.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians may use different diagnostic approaches, such as considering depression only after ruling out all possible medical diagnoses, and using antidepressants to rule in depression (Baik et al, 2005;Carney et al, 1998).…”
Section: Detection and Management Of Mdd In Primary Carementioning
confidence: 99%
“…Barriers to effective recognition of mental health disorders by PCPs include: "inadequate knowledge of the diagnostic criteria, uncertainty about the best questions to ask to evaluate whether those criteria are met, and time limitations inherent in a busy office setting" (Spitzer et al, 1994(Spitzer et al, , p. 1749. Many research studies have been conducted in order to understand, assess, and treat these disorders (American Family Physician, 2000;Baik et al, 2005;Cabana et al, 2002;CTPTSD, 2007;Grinage, 2003;Kessler et al, 2005;Lecrubier, 2004;Louch, 2009;Olfson et al, 2005;Pratt & Brody 2008;Staub, 2001), but few studies have examined the use of avatar technology to aid in the training of assessment and diagnosis of these disorders (Kenny et al, 2008;Satter et al, 2012;Triola et al, 2006). This research focused on evaluating computerbased training tools (Avatars) for training family physicians to better diagnose MDD and PTSD.…”
mentioning
confidence: 99%